(untitled) (Journal of Health Sciences, 2018)
Introduction: The most common cause of intracranial bleeding in younger patients and children are vascular anomalies. Digital subtractions angiography presents a gold standard in diagnostics of aneurisms and vascular malformations. Our aim is to present our experience in using computed tomography angiography in diagnosing arteriovenous malformations. Methods: We included 150 patients with acute non-traumatic intracranial hemorrhage diagnosed by non-contrast CT examination, after which they were subjected to CT angiography of the cerebral vessels, and then underwent maximum intense projection and volume rendering reconstruction. Results: Out of 150 patients with non-traumatic intracranial hemorrhage, in 121 (81%) a diagnosis of aneurysm was rendered, while in 8 (5%) arteriovenous malformation was found. In 29 (14%) patients cause of bleeding was not identified. Patients with arteriovenous malformations, were age 17-77 years, with mean age 42.75 years. Five (62.5%) of them were female patients and three (37.5%) were male. Conclusion: Spontaneous non-traumatic intracranial hemorrhage is a significant cause of morbidity and mortality. Computed tomography angiography is sufficiently specific and sensitive in diagnosis of arteriovenous malformations in our experience.